The association of pre-pregnancy body mass index and risk of pre-eclampsia - Nekkanti, Dhanusha; Rani C., Kavya; Kumar S., Vasantha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preeclampsia is a pregnancy-related condition characterized by new-onset hypertension and proteinuria. Preeclampsia is responsible for 20% to 80% of mortality among pregnant in developing countries. Preeclampsia may cause prematurity and fetal growth restriction. It is the most serious complication affecting 2-8% of all pregnancies. The mortality and morbidity rates among the babies of pre-eclampsia mothers is five times higher than that among babies born to healthy mothers. Objective: To find the association between pre-pregnancy Body Mass Index (BMI) and gestational weight gain with incidence of pre-eclampsia. Methods: Cross sectional Observational study was conducted among 140 cases. The study was conducted after obtaining approval from the ethics committee. Results: In this study, in 27.9% of cases overweight, and in 12.1% of cases obesity were seen. In 60.7% of cases severe preeclampsia, and 39.3% of cases mild preeclampsia was reported. Preeclampsia had no significant association with age, marital life, parity, but had a significant association with liquor, birth weight, and NICU admission. Conclusions: Pre pregnancy weight and Gestational weight gain were associated with high risk of preeclampsia.